Neotectonic structure and evolution of Lefkada island - ΛΕΚΚΑΣ Ε. Λ.; ΔΑΝΑΜΟΣ Γ. Δ.; ΛΟΖΙΟΣ Σ. Γ. (Bulletin of the Geological Society of Greece, 2001)
In this paper, the formations that participate in the geological structure of Lefkada island are described in detail, as well as two alpine tectonic phases that affected the island, together with the criteria for their evaluation. The tectonic fabric is then described and the mapped fault systems are analysed kinematically and geometrically through the time. The current geodynamic regime has found its expression on the island through a dense fault network that has overprinted the pre-existing thrust-related features and has been dominant throughout the Plioquaternary. The dense fault network has broken up the island in a multitude of independent fault blocks which are described; an attempt is also made to determine the relative movements among these fault-blocks. The recent geological history of Lefkada is characterized by basic periods of predominant compression, interrupted by brief extensional episodes, where gravitational movements are favoured.